2014
DOI: 10.1101/gr.177790.114
|View full text |Cite
|
Sign up to set email alerts
|

Widespread intron retention in mammals functionally tunes transcriptomes

Abstract: Alternative splicing (AS) of precursor RNAs is responsible for greatly expanding the regulatory and functional capacity of eukaryotic genomes. Of the different classes of AS, intron retention (IR) is the least well understood. In plants and unicellular eukaryotes, IR is the most common form of AS, whereas in animals, it is thought to represent the least prevalent form. Using high-coverage poly(A)+ RNA-seq data, we observe that IR is surprisingly frequent in mammals, affecting transcripts from as many as three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

108
771
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 596 publications
(885 citation statements)
references
References 59 publications
108
771
5
1
Order By: Relevance
“…Muscleblind-like protein 1 (MBNL1) is highly expressed in cardiac and skeletal muscles (52) and is a known regulator of mRNA splicing in these tissues (53,54). Intron retention has emerged as a widespread mechanism to regulate gene expression in different cell and tissue types as well as during stem cell differentiation (42,55,56). The finding that a retained intron at the 5′-UTR of Yy2 mRNA controls its translation underscores the intricate interplay between alternative splicing and translational control (57, 58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscleblind-like protein 1 (MBNL1) is highly expressed in cardiac and skeletal muscles (52) and is a known regulator of mRNA splicing in these tissues (53,54). Intron retention has emerged as a widespread mechanism to regulate gene expression in different cell and tissue types as well as during stem cell differentiation (42,55,56). The finding that a retained intron at the 5′-UTR of Yy2 mRNA controls its translation underscores the intricate interplay between alternative splicing and translational control (57, 58).…”
Section: Discussionmentioning
confidence: 99%
“…Primers Fw1 and Rv detect only variants B and ΔB (297-bp and 180-bp PCR products, respectively), whereas Fw2 and Rv amplify a 209-bp PCR product for variants A and B and a 92-bp PCR product for variants ΔA and ΔB. We examined Yy2 intron retention events in mESCs and EBs at days 4 and 6 postdifferentiation and measured the degree of intron retention using the percent intron retention (PIR) as a metric (42). The percentage of nonspliced variants (A and B) is higher in mESCs than in EBs, demonstrating that differentiation coincided with a marked reduction in intron retention (Figs.…”
Section: Yy2 Binds To the Regulatory Regions Of Key Genes For Esc Plumentioning
confidence: 99%
“…29 Given the fact that the introns in the linear form are engaged in the mechanism to minimize tissue-inappropriate gene expression, the biological function of intronic circRNAs is close to being discovered in the near future. 30 Beyond regulating microRNAs, circRNAs may bind to and sequester RNA-binding proteins (RBPs) via their conserved seed matches, resulting in the formation of large RNA-protein complexes. By detecting the covalent UV crosslinking between RNAs and RBPs, Memczak et al and Hansen et al proved the existence of the ribonucleoprotein (RNP) complex in plasma and further proved that the RNP complex was synthesized by combining circRNAs with miR-7 and the AGO protein.…”
Section: Biogenesis and Functionmentioning
confidence: 99%
“…We hypothesized that direct mRNA targets arising from splicing dysregulation would be less likely to belong to specific biological functions and would be structurally similar, whereas indirect targets might fall within particular pathways and impact gene expression as a result of activation of a developmental process or stress response (32)(33)(34)(35). Analysis of splice site strength showed that introns with greater degrees of retention had weaker 5′ and 3′ splice sites, as determined by consensus to canonical 5′ and 3′ splice site sequences (36), and retained introns were significantly higher in GC content compared with expression-and length-matched control introns ( Fig.…”
Section: Smnmentioning
confidence: 99%